2011
DOI: 10.1590/s0101-32892011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas de distúrbios osteomusculares em profissionais de educação física, atuantes em academias de Florianópolis-SC

Abstract: O objetivo do estudo foi verificar os sintomas de distúrbios osteomusculares - SDO em professores de academias e sua associação com jornada de trabalho, sexo e função exercida. O estudo foi do tipo transversal e contou com a participação de 54 professores. Os SDO foram verificados através do Questionário Nórdico de Sintomas Osteomusculares. A média de idade foi de 31,2 (± 6,9) anos. Verificou-se que 41 (75,9%) professores relataram SDO em pelo menos uma região anatômica nos últimos 12 meses e 25 (46,3%) nos úl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…Ambos os estudos relatados uti-lizaram questionários compostos por perguntas abertas, instrumentos diferentes daquele utilizado no presente estudo, os quais podem ter subestimado a medida de prevalência. Nesse sentido, em estudo recente, Mohr e colaboradores 18 relataram prevalência de dor no último ano em trabalhadores de Educação física atuantes em academias na cidade de Florianópolis/SC, utilizando o mesmo instrumento que o utilizado na presente pesquisa, de 75,9%, valor mais próximo ao de nosso estudo.…”
Section: Variáveisunclassified
See 1 more Smart Citation
“…Ambos os estudos relatados uti-lizaram questionários compostos por perguntas abertas, instrumentos diferentes daquele utilizado no presente estudo, os quais podem ter subestimado a medida de prevalência. Nesse sentido, em estudo recente, Mohr e colaboradores 18 relataram prevalência de dor no último ano em trabalhadores de Educação física atuantes em academias na cidade de Florianópolis/SC, utilizando o mesmo instrumento que o utilizado na presente pesquisa, de 75,9%, valor mais próximo ao de nosso estudo.…”
Section: Variáveisunclassified
“…Segmentos corporais como coluna lombar, joelho, pescoço e ombros foram citados no presente estudo, corroborando com Mohr et al 18 . Problemas musculoesqueléticos podem estar associados a inúmeros fatores, entre eles, aspectos biomecânicos envolvidos nas tarefas profissionais, elevado tempo de permanência na posição de pé, postura inadequada, repetitividade da tarefa e constante utilização de esforço físico 30 .…”
Section: Variáveisunclassified
“…Studies have identified that gym club instructors are susceptible to health issues, possibly related to the specific burden of their occupation [5][6][7] . In this sense, workers showed complaints regarding pains in several anatomical regions, especially the low back, the part of the body with the highest complaint prevalence, and knees, also presenting relevant percentages of complaints related to pain 6,8,9 . In addition, former studies reported that 53% of the aquatic modality instructors and 54% of the gym club instructors complained about pains resulting from occupational activities 7,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the characteristics of the work of professionals in the ACP, the following aspects were observed in this study: the orthostatic position, repetitive movements, long hours taught in the same work shift, impacting the provider on this outcome 7 . Moreover, such professionals also need to be attentive and aligned with their professional performance concerning the field of knowledge, the field of collective health, the Program's interventions principles and guidelines of The SUS and of Health Promotion should be also included 8 .…”
Section: Introductionmentioning
confidence: 99%
“…These were the two aspects defined to be investigated in this study, given the characteristics of work in the ACP that at the same time have characteristics of their core of activity that lead professionals to maintain in the orthostatic position for long hours, repetitive movements, teach several classes in the same work shift, so they are functions subject to different overloads 7 . As they also need to be attentive and aligned with a professional practice related to the field of knowledge, to the field of collective health, and should promote interventions based on the principles and guidelines of the SUS and Health Promotion 8 .…”
Section: Introductionmentioning
confidence: 99%